2013
DOI: 10.3415/vcot-12-06-0075
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injections of autologous platelet concentrates in dogs with surgical reparation of cranial cruciate ligament rupture

Abstract: Our results indicate that autologous PC might improve functional outcome after intra-articular cranial cruciate ligament repair. The effect of PC when using other repair procedures warrants additional studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 26 publications
4
21
0
Order By: Relevance
“…It has been reported that OA in rabbits treated with mesenchymal cells derived from adipose tissue showed radiographic changes at 20 weeks post infiltration [60]. Contrary to a previous study [60], here, improvement in the signs of OA was not seen, however a progression of the signs was not seen either during the six month study, similar to those results observed in human [61] and veterinary studies where Silva et al reported no significant differences in the radiographic exam between animals treated with PRP and control group after cranial cruciate ligament surgery [62]. The radiological analysis used in this study was inconclusive.…”
Section: Resultssupporting
confidence: 74%
“…It has been reported that OA in rabbits treated with mesenchymal cells derived from adipose tissue showed radiographic changes at 20 weeks post infiltration [60]. Contrary to a previous study [60], here, improvement in the signs of OA was not seen, however a progression of the signs was not seen either during the six month study, similar to those results observed in human [61] and veterinary studies where Silva et al reported no significant differences in the radiographic exam between animals treated with PRP and control group after cranial cruciate ligament surgery [62]. The radiological analysis used in this study was inconclusive.…”
Section: Resultssupporting
confidence: 74%
“…[7][8][9] Orthobiologic products (such as mesenchymal stem cells, bone marrow aspirate concentrate, and platelets rich products) are showing promise as safe and effective treatments for musculoskeletal diseases including osteoarthritis in people and animals. [10][11][12][13][14][15][16][17][18] Platelets possess anabolic and anti-inflammatory properties attributed to the delivery of various growth factors and cell signaling molecules that can modulate inflammation and promote tissue healing. 19,20 Because various methods exist to create different platelet-derived orthobiologics, we define platelet-rich plasma (PRP) as any product in which the concentration of platelets is increased relative to whole blood and partially or fully isolated from leukocytes and red cells within a plasma medium.…”
Section: Introductionmentioning
confidence: 99%
“…15,[20][21][22] More recently, the use of platelet-rich products has been shown to help alleviate pain and/or improve function including objective gait analysis in dogs with both naturally occurring and experimental models of OA. [13][14][15][16]23 We hypothesized that a single intra-articular injection of pure PRP (no white or red cells within the product) into the more severely affected stifle would cause substantial positive changes in kinetic gait symmetry in dogs with unilateral or bilateral chronic osteoarthritis attributed to long-term (>12 months) naturally occurring cranial cruciate ligament disease. A validated pressuresensitive walkway system was employed at baseline and every 4 weeks for 12 weeks post-treatment to determine peak vertical force (PF) and vertical impulse (VI) normalized to body weight in all limbs and calculate selected modified symmetry indices based on prior literature from PVF.…”
Section: Introductionmentioning
confidence: 99%
“…PRP has been mostly used in horses [6, 8] and dogs [9, 10] for the treatment of tenodesmic lesions and joint diseases. Furthermore, there are studies about the use of several PRP-related hemoderivatives for the treatment of mastitis [11], reproductive problems [12], and sole ulcers [13] in cows with encouraging results.…”
Section: Introductionmentioning
confidence: 99%